NITI Aayog: News published in Newspapers 2015 (Part-2) - NITI Aayog (NITI Aayog, Government of India, 2015)
On New Year’s Day, the Modi government set up NITI Aayog (National Institution for Transforming India) in place of the Planning Commission. The Prime Minister will head the new institution tasked with the role of formulating policies and direction for the government. Its governing council will comprise the Chief Ministers and the Lieutenant Governers of Union Territories.
News published in Newspapers
News published in Newspapers